Relationship Between Polyunsaturated Fatty Acids and Psychopathology in the NEURAPRO Clinical Trial - Berger, Maximus; Nelson, Barnaby; Markulev, Connie; Yuen, Hok Pan; Schäfer, Miriam R.; Mossaheb, Nilufar; Schlögelhofer, Monika; Smesny, Stefan; Hickie, Ian B.; Berger, Gregor E.; Chen, Eric Y. H.; de Haan, Lieuwe; et al. (Frontiers in Psychiatry, 2019)
Background Deficiencies in membrane polyunsaturated fatty acids (PUFA) such as omega-3 (n-3) fatty acids are thought to contribute to the pathophysiological processes underlying psychotic disorders. Emerging evidence suggests that the levels of PUFA are related to clinical symptoms but significant heterogeneity exists between studies. Here, we investigated associations of membrane PUFA with clinical symptoms and functioning in a large sample of individuals at ultra-high risk (UHR) for psychosis. Methods A total of 285 participants of the NEURAPRO clinical trial were investigated for erythrocyte PUFA levels, including the n-3 index, n-6/n-3 PUFA ratio, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Severity of general psychopathology (BPRS), psychotic symptoms (BPRS psychosis subscale), negative symptoms (SANS), manic symptoms (YMRS), depressive symptoms (MADRS) and functioning (SOFAS, GF-R, GF-S) were assessed concurrently. Partial correlation taking into account the effects of gender, age and smoking were used to examine the relationship between PUFAs and symptoms severity. Results The n-3 index negatively correlated with the severity of general psychopathology, psychotic symptoms, depressive symptoms and manic symptoms. The n-6/n-3 PUFA ratio positively correlated with severity of psychotic and depressive symptoms. The n-3 PUFA DHA negatively correlated with the severity of general psychopathology, positive, manic and depressive symptoms. EPA negatively correlated with manic symptoms. Nervonic acid, an n-9 monounsaturated fatty acid, positively correlated with general psychopathology, positive and negative symptoms, depressive symptoms and manic symptoms. The long-chain saturated fatty acid tetracosanoic acid positively correlated with general psychopathology, positive, manic and depressive symptoms. Conclusions Partially consistent with a previous study, psychotic symptoms, depressive symptoms and symptoms of mania were associated with several classes of FAs in the present study. These findings support the relevance of membrane fatty acids for the onset of psychotic symptoms and indicate that FAs should be further evaluated as biomarkers in the UHR for psychosis group.